Cultural Stereotypes about Spain in Foreign University Students: the Case of Slovenian Erasmus Students (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
The aim of this paper is to analyze the perception that Slovenian university students have about the Spanish culture and language. It is assessed how the perception of stereotypes has been affected after an Erasmus stay in Spain.Through a sociolinguistic test, the lexicon available to Slovenian university students of Spanish as a foreign langauge (level B2-C1) in several centers of interest (Spain, Spanish language, Spaniards, Spanish customs and traditions) is presented. It is further on compared between the group of students who heave never done a long stay in Spain with those who have been on Erasmus exchange in Spain for at least 5 months. In this way, we will try to answer the following question: To what extent does this type of inmersion influence the available lexicon of a foreign language and the stereotypes of its culture?
Keywords: stereotype; lexical availability; Spanish as a foreign language; Spain; Erasmus